2021
DOI: 10.3390/ma14061559
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sterilization Procedures on the Cutting Efficiency of Endodontic Instruments: A Systematic Review and Network Meta-Analysis

Abstract: Sterilization processes guarantee the sterility of dental instruments but can negatively affect instrument features by altering their physical and mechanical properties. The endodontic instrumentation can undergo a series of alterations, ranging from corrosion to variation in the cutting angle and then changes in the torsional properties and torsional fatigue resistance. This systematic literature review and meta-analysis aims to investigate alterations to the cutting efficiency of endodontic instruments that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…First outcome: Khabiri et The entire selection and screening procedure, as described in Table 2 (Ref. [7,40,41,[87][88][89][90]), is presented in the flowchart in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…First outcome: Khabiri et The entire selection and screening procedure, as described in Table 2 (Ref. [7,40,41,[87][88][89][90]), is presented in the flowchart in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%
“…A study has concluded that the adoption of a combination of mechanical, chemical, and ultrasonic cleaning methods as a standard protocol can provide complete cleaning of biological debris from endodontic instruments. All the endodontic files should be cleaned ultrasonically to remove the surface residue followed by autoclave procedures, which are considered gold standard sterilization procedures, and packed and stored to prevent cross-contamination by pathogenic bacterial species [5][6][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In today's scenario, this is the major hurdle in establishing a dental home where children are vulnerable for corona virus infections 13 . A systematic review and network meta-analysis by Dioguardi M et al, 2021 concluded that autoclave sterilization protocol must not be repeated more than 5 cycles as it reduces the cutting efficiency of steel and NiTi instruments 14 . Various studies prove that autoclaving may lead to fracture of the rotary instruments due to cyclic fatigue.…”
Section: Discussionmentioning
confidence: 99%